Race and the Yugoslav region Postsocialist, post-conflict, postcolonial? - Baker, Catherine (Theory for a Global Age, 2018)
"Numerous scholars have explored the former Yugoslavia as a site of ethnopolitical violence, shaped by the legacies of state socialism and its collapse. Others have adapted postcolonial thought to explain the marginalisation of the Balkans within Europe. But up to now, the question of race and what it means for the region has rarely been seriously considered. In this book, Catherine Baker connects critical race scholarship, global historical sociologies of race in translation, and south-east European cultural critique to situate the territories and collective identities of former Yugoslavia within the politics of race. Beginning with an investigation of demographic changes in popular culture, she traces the intersection of ideas and peoples to demonstrate how historically constituted racial formations organise Yugoslav politics in the present. South-east European studies treats race with exceptionalism, subsuming it into ethnicity and nationhood. Important interventions against this assumption often go unheard. Building on the work of transnational media scholars and intersectional feminist theorists, Baker argues for a mode of connection that positions the region within global legacies of colonialism, slavery and 'race', thereby revealing important truths about Yugoslavia's place in the world. Race and the Yugoslav region is essential reading for students and lecturers in postcolonial studies, post-Yugoslav/East European studies and global history. It will also be of interest to general readers seeking new ways of looking at the Yugoslav region in global context."